Success Factors to Promote Digital Learning Platforms: An Empirical Study From an Instructors Perspective - Noawanit Songkram; Suparoek Chootongchai; Sawaros Thanapornsangsuth; Hathaiphat Osuwan; Krerk Piromsopa; Yootthana Chuppunnarat; Nutthakorn Songkram (My University, 2023)
Digital learning platforms have been used as teaching aids in many countries; however, their success factors are not well established in Thailand. The primary objective of this study was to identify and confirm the success factors to promote digital learning platforms in Thailand from instructors’ perspectives. The sample included 788 Thai instructors. The confirmatory factor analysis (CFA) method indicates a good fit of a four-factor model to the observed data. The CFA construct revealed four success factors in promoting digital learning platforms: education policy, online classroom management, online learning system, and training method. The results explain the influence each of the four factors. Finally, this paper proposes guidelines for the promotion of digital learning platforms.
Keywords: Promotion (chess); Sample (material); Blended Learning; Virtual learning environment; Technology-Enhanced Education Studies